Some comments on the amendment to the Act on the shaping of the agricultural system of 23 July 2023 - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2023)
The aim of the deliberations is an assessment of certain solutions contained in the amendment to the Act on the shaping of the agricultural system in Poland, which entered into force on 16 October 2023. Among other things, the author concludes that the introduced amendments do not fully resolve the fundamental problems related to the interpretation of the Act. The solutions concerning the scope of exemptions from trading restrictions applicable to close family members, or transformations of businesses are imprecise and therefore cannot be given an unequivocal positive assessment. Repeated amendments to the Act (there have been 21 amendments since 2016) make the interpretation of its provisions increasingly complex. Therefore, a new law needs to be enacted, which will define precisely the framework of restrictions on the trading in agricultural real estate, implementing at the same time the constitutional protection of the family holding. This is a huge task for the legislator and for the doctrine of agricultural law in Poland.